South American precipitation changes simulated by PMIP3/CMIP5 models during the Little Ice Age and the recent global warming period - Díaz, Leandro Baltasar (2018)
Large climate variations have been detected from paleoclimatic records in some regions of South America during the last 500 years. Among them, the Altiplano and the subtropical Andes regions exhibited wetter-than-normal conditions during the 17th century within the paleoclimatic period known as Little Ice Age (LIA). On the other hand, both regions experienced drier-than-normal conditions in the second part of the 20th century in association with the recent global warming period (GWP). This study provides an assessment of the ability of four models of the third phase of the Paleoclimate Modelling Intercomparison Project (PMIP3)/fifth phase of the Coupled Model Intercomparison Project (CMIP5) experiments in reproducing those regional rainfall changes and the associated large-scale circulation features. Climate models can represent qualitatively the temperature changes observed in South America in both periods, LIA and GWP, as compared to the control run, but they do not properly describe the associated precipitation changes. However, they can simulate, in some extent, the large-scale circulation changes that previous works identified as important in driving the precipitation changes in both regions. Therefore, the assessment allows to detect the following changes in LIA (GWP): (a) equatorwards (polewards) displacement of the southern branch of the Hadley cell, in turn associated with wetter (drier) conditions in subtropical south America; (b) negative (positive) upper-level zonal wind changes related with positive (negative) December, January and February (DJF) rainfall changes in the Altiplano; and (c) positive (negative) low-level zonal wind changes associated to positive (negative) JJA rainfall changes in the subtropical Andes, being in turn related to hemispheric wind changes resembling a negative (positive) phase of the southern annular mode.